AFFIRMING POSITION OF WOMEN IN PATRIARCHY SYSTEM IN LYNN NOTTAGE’S PLAY SCRIPT BY THE WAY, MEET VERA STARK (2013) - Indah Lestari; Kurnia Ningsih (Universitas Negeri Padang, 2019)
The aim of this analysis is to expose the issue about affirming position of women in patriarchy system which is done by patriarchal in order to subordinates the women. It is also intended to find out how the contribution of dramatic elements (character, plot/conflict, setting and stage direction) in revealing the issue of affirming position of women in patriarchy system. This analysis is done through text and contex based interpretation which is related to the concept of patriarchy by Kamla Bhasin and beauty by Naomi Wolf. The result of this analysis shows how patriarchy system strengthens the position of women as subordinate and less important person in patriarchal society that can be seen from limitation of career and its development as well as physical appearance.